Cultural Influence towards Corruption: Perceptions of Construction Practitioners in Indonesia - Hansen, Seng (PRESUNIVE CIVIL ENGINEERING JOURNAL, 2025)
The construction sector is one of the most vulnerable sectors to corruption. Previous publications have examined the causes, types, impacts, and strategies for preventing and eradicating corrupt practices in the construction sector. This research, however, focuses on the influence of cultural aspects on corrupt practices in the Indonesian construction sector. Through a mixed-method approach, this research identifies various forms of corruption in the construction sector and measures construction practitioners’ perceptions regarding the frequency of these corrupt practices. In summary, 14 forms of corrupt practices can occur at four stages of construction procurement. The analysis results also show practitioners’ perception of corruption as a norm in the construction business. This is motivated by the influence of cultural aspects in Indonesian society, especially related to the practice of connections and insiders, as well as a permissive attitude towards corruption. The results of this research contribute as a reference for stakeholders in understanding the influence of cultural aspects comprehensively so that they can take effective steps in establishing an anti-corruption culture in Indonesia.